Measuring and Calculative Complex for Registration of Quasi-Static and Dynamic Processes of Electromagnetic Irradiation - V. I. Ovchinnikov; E. A. Doroshkevich; S. M. Usherenko; A. S. Kalinichenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper is devoted to the development of measuring device to register dynamic processes of electromagnetic irradiation during the treatment of materials with energy of explosion. Standard units to register main parameters of the explosion do not allow predict and control results of the process. So, to overcome disadvantages of former control units a new one has been developed applying Hall’s sensors. The device developed allows effectively register of the inductive component of the electromagnetic irradiation in wide range of temperature for many shot-time processes.